The non-sovereign self, responsibility, and otherness : Hannah Arendt, Judith Butler, and Stanley Cavell on moral philosophy and political agency - Kelz, Rosine 1981- (International political theory, 2016)
"In times of globalization, critiques of sovereignty have become a pervasive feature of political theory. This book investigates how forms of political association and the responsibilities we have for others could be informed by non-sovereign concepts of the self. Placing the reader in dialogue with Hannah Arendt, Judith Butler and Stanley Cavell, it engages with debates surrounding the key concepts of identity, becoming, agency and ethical responsibility - specifically in terms of a 'non-sovereign self'. Non-sovereignty highlights how thought, language, and ultimately one's very survival depend on social relationships. While non-sovereign accounts of human social life have become widely accepted, there is an ongoing debate about definitions and roles of key terms such as 'finitude' or 'relationality' and the consequences they have for political thought. Drawing on Hannah Arendt, Judith Butler and Stanley Cavell, this book addresses contemporary theoretical and political debates in a broader comparative perspective and rearticulates the relationship between ethics and politics by highlighting those who are currently excluded from our notions of political community"--